1986
DOI: 10.1037/0022-0167.33.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Relation between conceptual level and counseling-related tasks: A meta-analysis.

Abstract: Conceptual systems theory (CST) has been used to predict the relation between a counselor's conceptual level (CL) and the counseling process. A meta-analysis was used to review 24 studies that applied CST in one of the following two ways: (a) to investigate the effect of CL on the counselor's performance and (b) to investigate the matching of CL and environmental structure. The results corroborated the predictive power of CST in the context of the counseling situation. First, the prediction that counselors who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 31 publications
7
68
0
Order By: Relevance
“…Although there has been some contro-versy about the extent to which conceptual level varies according to trainees' experience and training (see e.g., Holloway, 1987), it is generally understood as a relatively stable attribute. In their meta-analysis, Holloway and Wampold ( 1986) concluded that trainees low in conceptual level preferred a more structured environment, whereas those higher in conceptual level were more comfortable with a relatively less structured training environment. Winter and Holloway (1991) have also found that trainees with higher conceptual level were less concerned about evaluation and requested more critical feedback from their supervisors.…”
Section: The Role Of Individual Differences In Supervisionmentioning
confidence: 97%
“…Although there has been some contro-versy about the extent to which conceptual level varies according to trainees' experience and training (see e.g., Holloway, 1987), it is generally understood as a relatively stable attribute. In their meta-analysis, Holloway and Wampold ( 1986) concluded that trainees low in conceptual level preferred a more structured environment, whereas those higher in conceptual level were more comfortable with a relatively less structured training environment. Winter and Holloway (1991) have also found that trainees with higher conceptual level were less concerned about evaluation and requested more critical feedback from their supervisors.…”
Section: The Role Of Individual Differences In Supervisionmentioning
confidence: 97%
“…In cases where duplicate publication of the same study was encountered, the highest prestige source was coded (Holloway and Wampold 1986).…”
Section: Quantiþcation Of Studiesmentioning
confidence: 99%
“…Given the importance of cognitive skill development, it seems ironic that most research to date has focused on performance skills (i.e., empathy, self-disclosure, confrontation) even though it has been argued that the development of the cognitive counseling skills are equally, if not more, important in the development of the counselor-in-training (Fuqua et al, 1984). In fact, as early as 1980, Holloway and Wolleat noted that counselors with more developed cognitive abilities were better able to produce effective clinical hypotheses; subsequent work has supported their conclusions (e.g., Holloway & Wampold, 1986). Furthermore, there is some evidence that counselors who produce better hypotheses are more effective clinicians (Morran, Kurpius, Brack, & Rozecki, 1994).…”
mentioning
confidence: 83%